The Illusion of Transparency and Its Relationship to Certain Variables Among University Students - Kadhim, Hajar Aqeel; Al-Daghestani, Sanaa Issa (Journal of Posthumanism, 2025)
The Illusion of Transparency is a cognitive bias that leads individuals to overestimate the extent to which their thoughts and emotions are apparent to others. It has a strong impact on individuals in a wide range of situations. People suffer from this illusion due to a natural egocentric bias, which causes them to rely heavily on their own perspective when attempting to consider the perspectives of others. This leads to overestimating how much others notice their emotional state, especially when they feel anxious about speaking in public. The current study aimed to measure the level of the illusion of transparency among university students, and to examine the significance of the differences according to gender (male – female), specialization (scientific – humanistic), and academic year (second – fourth). The study sample consisted of 400 students selected using the stratified random sampling method with equal distribution. After collecting and statistically analyzing the data, the results showed the following: University students demonstrated a high level of the illusion of transparency (16.5), indicating that they tend to overestimate the visibility of their feelings and emotions to others. There was a statistically significant difference in the illusion of transparency based on gender in favor of females, and based on specialization in favor of the humanities. However, there was no statistically significant difference based on academic year.